Increasing the geometric field of view in head mounted displays through proprioceptive task and multimodal feedback for effective close range interaction. - Yang U; Kim GJ (Behaviour & Information Technology)
This article explores the synergistic interaction among the geometric field of view (GFOV), proprioceptive interaction and multimodal feedback in a virtual environment. We hypothesise that, with proprioceptive interaction and multimodal feedback, the GFOV can be set larger than its reference value originally set to give similar distance perception when viewed with a given physical field of view of a head mounted display. This in turn would help a user carry out a task more effectively with the increased visibility. We tested our hypothesis with an experiment to measure the user's change in distance perception according to different values of egocentric GFOV and task/feedback conditions (15 subjects). Our experimental results have shown that, when coupled with proprioceptive interaction, the GFOV could be increased up to 170% of the reference without introducing change in user's distance perception. When additional visual and tactile feedback was introduced, the GFOV could be increased up to 200%. The results offer a useful guideline for designing multimodal interfaces for close range spatial tasks in virtual environments. In addition, it demonstrates one way to overcome the inadequacy of the narrow physical fields of view often found in most general purpose head mounted displays.